2003
DOI: 10.1080/1360786031000101148
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression in older adults with multiple sclerosis (MS): Comparison with a matched sample of younger adults

Abstract: The study considered for the first time depression in older adults with multiple sclerosis (MS). Depression symptom scores of 27 persons aged over 65 years who were part of a large study of persons with MS (n = 529), were compared with those of a matched sample of younger adults from the same study. The association between cognitive (attitudinal) variables known to explain significant variance in depressive symptoms in younger adults with MS was then considered in the older adult sample. Consistent with findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
1
18
1
1
Order By: Relevance
“…Several studies found no significant gender-related difference in the incidence of depression [6,15,34]. Several community and tertiary centre studies have reported that older patients with MS report fewer symptoms of depression than younger patients [15,30,35]. We did not find any correlations between depression and patient age or gender.…”
Section: Resultscontrasting
confidence: 44%
“…Several studies found no significant gender-related difference in the incidence of depression [6,15,34]. Several community and tertiary centre studies have reported that older patients with MS report fewer symptoms of depression than younger patients [15,30,35]. We did not find any correlations between depression and patient age or gender.…”
Section: Resultscontrasting
confidence: 44%
“…However, in the Galeazzi et al (2005) study, age was not associated with either a current or past episode of MDD. Compared with older individuals with MS (M = 70), younger persons (M = 46) scored significantly higher on a measure of depressive symptoms (t (26) = 2.41, p <.05), indicating that they experienced more of these symptoms (Kneebone, Dunmore, & Evans, 2003).…”
Section: Primary Progressive Ms (Ppms)mentioning
confidence: 99%
“…These include cognitive biases towards negative information and attributions and unhelpful or negative beliefs about oneself, the world and the future. However, only a handful of studies have been conducted so far (20)(21)(22)(23)(24) and these factors have not been studied in relation to broader adjustment outcomes such as social and role functioning and quality of life. Another variable deemed worthy of exploration is people's beliefs about experiencing and expressing negative emotions.…”
mentioning
confidence: 99%